## 3x+5=x+9 is- =-..​

Question

3x+5=x+9 is….
………………​

in progress 0
7 months 2021-10-07T21:58:42+00:00 2 Answers 0 views 0

Step-by-step explanation:

Simplifying

3x + -5 = x + -9

Reorder the terms:

-5 + 3x = x + -9

Reorder the terms:

-5 + 3x = -9 + x

Solving

-5 + 3x = -9 + x

Solving for variable ‘x’.

Move all terms containing x to the left, all other terms to the right.

Add ‘-1x’ to each side of the equation.

-5 + 3x + -1x = -9 + x + -1x

Combine like terms: 3x + -1x = 2x

-5 + 2x = -9 + x + -1x

Combine like terms: x + -1x = 0

-5 + 2x = -9 + 0

-5 + 2x = -9

Add ‘5’ to each side of the equation.

-5 + 5 + 2x = -9 + 5

Combine like terms: -5 + 5 = 0

0 + 2x = -9 + 5

2x = -9 + 5

Combine like terms: -9 + 5 = -4

2x = -4

Divide each side by ‘2’.

x = -2

Simplifying

x = -2

Simplifying

3x + -5 = x + -9

Reorder the terms:

-5 + 3x = x + -9

Reorder the terms:

-5 + 3x = -9 + x

Solving

-5 + 3x = -9 + x

Solving for variable ‘x’.

Move all terms containing x to the left, all other terms to the right.

Add ‘-1x’ to each side of the equation.

-5 + 3x + -1x = -9 + x + -1x

Combine like terms: 3x + -1x = 2x

-5 + 2x = -9 + x + -1x

Combine like terms: x + -1x = 0

-5 + 2x = -9 + 0

-5 + 2x = -9

Add ‘5’ to each side of the equation.

-5 + 5 + 2x = -9 + 5

Combine like terms: -5 + 5 = 0

0 + 2x = -9 + 5

2x = -9 + 5

Combine like terms: -9 + 5 = -4

2x = -4

Divide each side by ‘2’.

x = -2

Simplifying

x = -2